Development of Rural Women's Micro Enterprises - Muksin Muksin; Binti Vivi Nur Anggraini (Jurnal Manajemen Agribisnis dan Agroindustri, 2025)
This research is motivated by the role of women farmers in the management of agricultural products in Jember Regency. One way to increase the value of agricultural products is through agroindustry. In Termap Hamlet, Kemuning Lor Village, Jember Regency, there is a Cassava Chips Business managed by women farmers. Farmer women are the wives or families of farmers who own cassava commodity agricultural land whose daily life is as a housewife (IRT). The Cassava Chips business was established in 2012 and started from a small production scale with modest capital. The objectives of the research are: (1). Analyzing the internal and external factors of environmental conditions in the Cassava Chips Business (2). Formulating alternative business development strategies (3) Developing the right strategy priorities to be applied to the Cassava Chips Business. The method used in this study is by analyzing the company's internal and external factors and then analyzing using a SWOT matrix and QSPM analysis.